Endoscopic ultrasound in the diagnosis of acinar cell carcinoma of the pancreas: contrast-enhanced endoscopic ultrasound, endoscopic ultrasound elastography, and pathological correlation - Chantarojanasiri, Tanyaporn; Hirooka, Yoshiki; Kawashima, Hiroki; Ohno, Eizaburo; Yamamura, Takeshi; Funasaka, Kohei; Nakamura, Masanao; Miyahara, Ryoji; Ishigami, Masatoshi; Watanabe, Osamu; Nakaguro, Masato; Shimoyama, Yoshie; Nakamura, Shigeo; Goto, Hidemi (Endoscopy International Open, 2016)
We report a case series of five patients with pancreatic acinar cell carcinoma who received surgical treatment and compared the preoperative contrast-enhanced endoscopic ultrasound (EUS) and EUS elastography patterns with the surgical specimens. The contrast-enhanced EUS indicated vascular tumors with gradual enhancement in four patients and a hypovascular tumor in one patient. The elastography indicated an elastic score of 3 (hard lesion with softer border) in two patients and a score of 5 (hard lesion, which included the surrounding area) in two patients. In tumors with an elastic score of 5, the pathology exhibited abundant hyalinizing fibrous stroma or massive tumor invasion to the surrounding tissue. We concluded that acinar cell carcinoma of the pancreas has various patterns of EUS contrast-enhancement and elastography, depending on the pathologic phenotype.